2002
DOI: 10.1107/s0108768101020845
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the structure and phase transitions in the novel A-site substituted distorted perovskite compound Na0.5Bi0.5TiO3

Abstract: Rietveld neutron powder profile analysis of the compound Na(0.5)Bi(0.5)TiO(3) (NBT) is reported over the temperature range 5-873 K. The sequence of phase transitions from the high-temperature prototypic cubic structure (above 813 K), to one of tetragonal (673-773 K) and then rhombohedral structures (5-528 K) has been established. Coexisting tetragonal/cubic (773-813 K) and rhombohedral/tetragonal (with an upper temperature limit of 145 K between 528 and 673 K) phases have also been observed. Refinements have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
661
3
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 911 publications
(721 citation statements)
references
References 22 publications
50
661
3
7
Order By: Relevance
“…[18][19][20][21][22][23][24][25] Our work shows there are two types of NBT based on the level of nonstoichiometry (resistive stoichiometric NBT and conducting Bi-deficient NBT). It's not clear whether the NBT samples used in the structural studies reported in the literature are resistive or conducting and whether or not these two electrically distinct materials have the same crystal structure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[18][19][20][21][22][23][24][25] Our work shows there are two types of NBT based on the level of nonstoichiometry (resistive stoichiometric NBT and conducting Bi-deficient NBT). It's not clear whether the NBT samples used in the structural studies reported in the literature are resistive or conducting and whether or not these two electrically distinct materials have the same crystal structure.…”
Section: Discussionmentioning
confidence: 99%
“…For 18 O tracer diffusion measurements, the standard procedure for introducing an 18 O penetration profile into a solid from a large volume of gas was employed. 32,33 Dense samples (relative density > 95%) were annealed in highly enriched 18 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations